STUDENTS IN ISLAMIC EDUCATION HADITH PERSPECTIVE - Rasyid Anwar Dalimunthe; Muhlison Muhlison (Proceeding International Seminar of Islamic Studies, 2023)
In government public schools they are called students or pupils, in the world of Islamic boarding schools they are called santri, at higher education levels they are usually called students, and some official institutions call their students by certain names, such as Praja IPDN, military academy trainees and so on. On this basis, these terms are generally lumped together with the names of the students. Learners are an integral part of the education system and are processed to become quality human beings in accordance with national education goals. The purpose of writing this article is to find out in terms of hadith about who the students are and what students should be in Islamic education. This research includes library research, namely research library materials or literature related to research problems by selecting, reading, studying and researching books or other relevant written sources. The approach used is an analytical descriptive approach. The author uses a "qualitative" analysis strategy, this strategy means that the analysis starts from the data and leads to general conclusions. As for the findings obtained after reviewing and looking at several books of hadith, students in Islamic education are every individual Muslim. Meanwhile, students should have sincere intentions in undergoing the educational process, be patient and put their trust in Allah SWT. with all educational obstacles, obey the rules in Islamic educational institutions, earnestly carry out the educational process without being lazy. And finally, students must study thoroughly, so that there are no disconnected grade levels or the knowledge taught by the educator.